A women's worth: exploring ethnic minority female entrepreneurs' experiences in Sri Lanka - Sahira, Samimeer; Surangi, H.A.K.N.S. (Management and Entrepreneurship: Trends of Development, 2022)
Women, particularly minority women, remain underrepresented in entrepreneurial activities and continue establishing ventures in low-growth sectors. This qualitative research explores ethnic minority female entrepreneurs' experiences by focusing on why women might choose entrepreneurship as a career choice and their constraints. The study adopts a social constructionist approach, specifically narrative design. Data were collected through in-depth interviews with ten minority female entrepreneurs who founded ventures in Sri Lanka. Thematic analysis was used, and the transcripts were reviewed and explored, codes created, emerging themes identified, and interpretation with explanation building undertaken. Findings revealed that perception of ethnic discrimination discourages some ethnic minority businesses from applying for bank loans. As a result, female entrepreneurs perceive higher financial barriers to their business. Moreover, the results highlight the importance of transnational family networks within all aspects of the business and suggest that these links can sometimes provide a fertile source of new business ideas and limit innovation and decisions shaped by cultural norms. The findings can support facilitating and promoting entrepreneurship among ethnic minority female entrepreneurs. It could be valuable to further our understanding of the role of ethnic minority females and their experiences of combining entrepreneurship and business. JEL Clasification: C35, L26, L31.